2016
DOI: 10.1155/2016/7462014
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Molecular Imaging of Alzheimer’s Disease

Abstract: Alzheimer's disease is a complex neurodegenerative disease affecting millions of individuals worldwide. Earlier it was diagnosed only via clinical assessments and confirmed by postmortem brain histopathology. The development of validated biomarkers for Alzheimer's disease has given impetus to improve diagnostics and accelerate the development of new therapies. Functional imaging like positron emission tomography (PET), single photon emission computed tomography (SPECT), functional magnetic resonance imaging (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 168 publications
1
8
0
Order By: Relevance
“…In general, measurement of the effect of CR by [ 18 F]FDG PET-CT opens the possibility to monitor CR-induced neuroprotection using a noninvasive method and, in particular, in a longitudinal manner. In addition to [ 18 F]FDG-PET/CT, 1H-MRS represents another in vivo technique which allows for the characterization of metabolic changes in AD brains [ 43 , 44 ]. NAA, as a representative metabolite of neuronal integrity, is found to be reduced in AD, indicating neuronal malfunction either due to diminished neuronal density, neuronal cell loss, or partially reversible neuronal dysfunction [ 45 ], and correlates with disease progression [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, measurement of the effect of CR by [ 18 F]FDG PET-CT opens the possibility to monitor CR-induced neuroprotection using a noninvasive method and, in particular, in a longitudinal manner. In addition to [ 18 F]FDG-PET/CT, 1H-MRS represents another in vivo technique which allows for the characterization of metabolic changes in AD brains [ 43 , 44 ]. NAA, as a representative metabolite of neuronal integrity, is found to be reduced in AD, indicating neuronal malfunction either due to diminished neuronal density, neuronal cell loss, or partially reversible neuronal dysfunction [ 45 ], and correlates with disease progression [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Brain morphometry based on high resolution MRI is considered a proxy of neuronal loss in humans ( Bobinski et al, 2000 ). Proton magnetic resonance spectroscopy ( 1 H-MRS) is an in-vivo technique to analyze neuronal functional viability in transgenic animal models ( Mlynárik et al, 2012 ) and human studies ( Arora and Bhagat, 2016 ). Each observable metabolite can potentially serve as a marker being representative for pathological processes at a molecular or cellular level.…”
Section: Introductionmentioning
confidence: 99%
“…Here, a pre-clinical study reported that mice carrying the human APOE 4 isoform (hApoE4-TR) showed decreased [ 18 F]FDG uptake [18]. Complementary to [ 18 F] FDG-PET/CT, proton magnetic resonance spectroscopy ( 1 H-MRS) allows characterization of neurochemical alterations in AD brains [19]. N-Acetylaspartate (NAA) is considered to reflect neuronal mitochondrial function [20,21].…”
Section: Introductionmentioning
confidence: 99%